Conserving canvas - Schwarz, Cynthia (Paintings conservator); McClure, Ian; Coddington, James (Getty Conservation Institute, 2023)
"A collection of international case studies concerning the structural care and conservation of paintings on canvas, drawn from the proceedings of the October 2019 symposium Conserving Canvas"--